A framework for the practice of group supervision - Thabathi, LJV; Mamasela, SC (Social Work/Maatskaplike Werk, 2001)
The aim of this study was to enhance the appropriate utilisation of group supervision, which was under-utilise d in this part of the country (Northern Province). The end product of the study was a proposed framework for the practice of group supervision. GROUP SUPERVISION DEFINED Group supervision is a regular meeting of a group of supervisees with a designated supervisor for the purposes of furthering their understanding of themselves as clinicians, or their clients or of service delivery in general, and who are aided in their endeavour by their interactions with each other and with their supervisor in the context of the group process (Bernard & Goodyear, 1989:72).